The Petunia GRAS Transcription Factor ATA/RAM1 Regulates Symbiotic Gene Expression and Fungal Morphogenesis in Arbuscular Mycorrhiza. Issue 3 (13th May 2014) - Rich, Mélanie K.; Schorderet, Martine; Bapaume, Laure; Falquet, Laurent; Morel, Patrice; Vandenbussche, Michiel; Reinhardt, Didier
Abstract : A petunia transcription factor affects symbiotic gene expression and is required for arbuscule development and restriction of fungal colonization in the root tip. Abstract: Arbuscular mycorrhiza (AM ) is a mutual symbiosis that involves a complex symbiotic interface over which nutrients are exchanged between the plant host and the AM fungus. Dozens of genes in the host are required for the establishment and functioning of the interaction, among them nutrient transporters that mediate the uptake of mineral nutrients delivered by the fungal arbuscules. We have isolated in a genetic mutant screen a petunia ( Petunia hybrida ) GIBBERELLIC ACID INSENSITIVE, REPRESSOR of GIBBERELLIC ACID INSENSITIVE, and SCARECROW (GRAS)-type transcription factor, ATYPICAL ARBUSCULE (ATA), that acts as the central regulator of AM -related genes and is required for the morphogenesis of arbuscules. Forced mycorrhizal inoculations from neighboring wild-type plants revealed an additional role of ATA in restricting mycorrhizal colonization of the root meristem. The lack of ATA, which represents the ortholog of REQUIRED FOR ARBUSCULAR MYCORRHIZA1 in Medicago truncatula, renders the interaction completely ineffective, hence demonstrating the central role of AM -related genes for arbuscule development and function.